SYNTHESIS OF COPOLYMER OF ACRYLAMIDE AND 9-ACRYLAMIDODECANOIC ACID (AMAADA) FROM PALM OIL FOR ENHANCED OIL RECOVERY (EOR) - (NIM : 30510301), DESNELLI
The increase in population led to the increasing need of fuel, but unfortunately, the oil production is declining. One of the reasons is due to old production wells which actually may still contain oil being trapped in the reservoir. In the primary and secondary stages of production this oil cannot be removed optimally into the production well. This problem can be overcome by using tertiary stage known as Enhanced Oil Recovery (EOR). One of the EOR methods developed at present is the use of polymers which is added into the reservoir to increase the viscosity of formation water so as to push the oil to the production wells. Most of the polymeric materials widely used in EOR techniques is polyacrylamide made from fossil raw materials. In this study, an alternative polymer for EOR has been synthesized from renewable materials. The material used is palm oil, containing a major component of long-chain fatty acids that has been developed as raw material for the chemical industries. As one of the largest palm oil producers in the world, Indonesia has an abundant natural resources. Therefore, this potency should be used to develop chemical industries, in particular polymers for EOR applications. The aim of this research is to synthesize polymers derived from crude palm oil (CPO) which can be applied in EOR. There are several stages in this research, namely: 1. synthesis of monomers derived from CPO, 2. synthesis of polymers and 3. characterization of polymers for EOR application. The synthesis of monomers consists of three steps including esterification of oleic acid, cross olefin metathesis catalyzed by a Grubbs II catalyst by using olefin with methyl oleic or palm oil fatty acids methyl esters (FAME) to produce methyl 9-decenoic, and finally synthesis of acrylamide derivative, namely 9-acrylamidodecanoic acid (AADA). The characterization of products has been carried out by using NMR, GC-MS and FTIR spectroscopies. The results show that methyl 9-decenoic has been successfully synthesized from methyl oleic and palm oil FAME. However, the obtained methyl 9-decenoic was still in an unpurified form. By using a commercial 9-decenoic acid, the acrylamide derivative monomer was obtained under Ritter condition by reaction between acrylonitrile and 9-decenoic acid catalyzed by concentrated sulfuric acid. The structure of the resulting monomer was established by NMR and FTIR spectroscopy data. In the second stage of this research, the synthesis of polymers has been done by copolymerization between acrylamide (AM) and its derivative (AADA) with various composition in mol ratio as follows: 98:2 (AMAADA2), 95:5 (AMAADA5), 80:20 (AMAADA20) and 100: 0 (PAM). The symbols in brackets stand for the copolymers being formed. The copolymerization was catalyzed by 1% mol of ammonium persulfate and the products were precipitated by acetone. The synthesized polymers were characterized by spectroscopy data, including NMR and FTIR, and thermal analysis of DSC/TGA. The NMR and FTIR spectroscopy data show that the copolymers have successfully been synthesized. Furthermore, the thermal analysis shows that the copolymers have a better thermal stability than the PAM homopolymer. The AMAADA20 shows a higher thermal stability than both AMAADA2 and AMAADA5. Increasing content of AADA in the copolymer results in higher thermal stability of the copolymer. The intrinsic viscosity of the copolymer decreases by increasing AADA content in the copolymers as a result of intramolecular interactions which are more dominant in dilute solutions. The final stage of this research has been done to study the possibilities of the resulting polymers for EOR applications. This study includes the effects of concentration, salinity and temperature on polymer viscosity; in which the synthesized polymers synthesized have been compared to two kinds of commercial polymers. The viscosity of the polymer increases with increasing content of AADA monomer. The effect of salinity on viscosity has been studied using various salts such as NaCl, CaCl2 and KCl. The analysis shows that the viscosity of the polymer decreases with increasing salt content and tends to be stable with increasing salt concentration. The effect of temperature on viscosity has been carried out at various temperatures ranging from 30 to 90 Ã‚Â°C. The analysis shows that the polymer viscosity decreases with increasing temperature. The AMAADA20 copolymer has a better thermal stability than PAM and commercial polymers. From this research it can be concluded that methyl 9-decenoic, 9-acrylamidodecanoic acid monomers and the AMAADA copolymers have been successfully synthesized; proven by the characterization of those products. The rheology tests show that the AMAADA copolymers have higher resistances to salinity and temperature than PAM. The AMAADA20 copolymer has a higher thermal stability than the two commercial polymers, while its resistance to salinity is comparable to both commercial polymers.